A fast and simple PFAS extraction method utilizing HR–CS–GFMAS for soil samples. (May 2022) - Simon, Fabian; Gehrenkemper, Lennart; von der Au, Marcus; Wittwer, Philipp; Roesch, Philipp; Pfeifer, Jens; Cossmer, Antje; Meermann, Björn
Abstract: Here, we describe an optimized fast and simple extraction method for the determination of per- and polyfluorinated alkyl substances (PFASs) in soils utilizing high resolution-continuum source-graphite furnace molecular absorption spectrometry (HR–CS–GFMAS). To omit the bias of the solid phase extraction (SPE) step commonly used during the analysis of extractable organically bound fluorine (EOF) we optimized a fast and simple SPE-free extraction method. The developed extraction method consists of a liquid-solid extraction using acidified methanol without any additional SPE. Four extraction steps were representative to determine a high proportion of the EOF (>80% of eight extractions). Comparison of the optimized method with and without an additional SPE clean-up step revealed a drastic underestimation of EOF concentrations using SPE. Differences of up to 94% were observed which were not explainable by coextracted inorganic fluoride. Therefore, not only a more accurate but also a more economic as well as ecologic method (bypassing of unnecessary SPE) was developed. The procedural limit of quantification (LOQ) of the developed method was 10.30 μg/kg which was sufficient for quantifying EOF concentrations in all tested samples. For future PFAS monitoring and potential regulative decisions the herein presented optimized extraction method can offer a valuable contribution. Graphical abstract: Image 1 Highlights: New optimized extraction method for PFAS sum parameter analysis in soil samples. Liquid solid extraction enabled separation of extractable inorganic fluoride and organic bound fluorine. Bypassing of error prone SPE. Fast, sensitive and selective fluorine detection applying HR–CS–GFMAS.